Exploring Chromogranin A (CgA) as a Diagnostic Marker in Hypothermia-Related Deaths: Two Case Studies and a Literature Review - Luca Tomassini; Erika Buratti; Giulia Ricchezze; Roberto Scendoni (Diagnostics)
Background: Hypothermia, occurring when core temperature drops below 35 °C, can lead to death when the body’s heat loss exceeds its heat production. This study investigates two hypothermia-related deaths, exploring the utility of immunohistochemistry, specifically focusing on chromogranin A (CgA) as a potential diagnostic tool. The aim is to assess whether CgA expression in neuroendocrine tissues can be considered a reliable indicator of premortem stress response in fatal hypothermia cases. Case Presentation: In the first case, a 67-year-old man was found on a snowy road 24 h after his disappearance. The autopsy revealed cold-induced skin lesions, gastric hemorrhages, and cerebral and pulmonary edema. Positive CgA immunostaining was observed in the pancreatic islets and adrenal medulla. In the second case, a 49-year-old man was found dead in a wooded area with indications of suicide. Both cases were examined with attention to macroscopic findings and histological samples from major neuroendocrine organs. As in previous cases, CgA immunostaining was positive in the pancreatic islets and adrenal medulla. Staining intensity was moderate to strong, consistent with heightened neuroendocrine activity, supporting the hypothesis of systemic stress prior to death. Conclusions: Although CgA is a potentially valuable adjunct in hypothermia diagnosis, careful consideration of cadaveric preservation is emphasized, particularly when bodies are preserved before autopsy. Further studies with larger sample sizes are needed to confirm its diagnostic specificity and to distinguish true pathological patterns from postmortem artifacts.